2019
DOI: 10.1016/j.jairtraman.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the volatility of international visitor arrivals to New Zealand

Abstract: International visitor arrivals are considered to be a major source of foreign exchange, tourism-related employment and other tourism-related activities. This study used SARIMAX/(E)GARCH volatility models to forecast visitor arrivals by air transport to New Zealand from its eight key tourist source markets the United Kingdom (UK) and the United States (US)) and control macroeconomic factors together with global and regional structural changes. The empirical models reveal that the macroeconomic factors contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…The authors found evidence to suggest that a negative shock would result in less uncertainty for Dominica, Maldives and Seychelles, while the opposite is true for Barbados, Fiji and Cyprus. Similar asymmetric effects of tourist demand shocks were also reported by Balli et al (2019).…”
Section: Literature Reviewsupporting
confidence: 80%
“…The authors found evidence to suggest that a negative shock would result in less uncertainty for Dominica, Maldives and Seychelles, while the opposite is true for Barbados, Fiji and Cyprus. Similar asymmetric effects of tourist demand shocks were also reported by Balli et al (2019).…”
Section: Literature Reviewsupporting
confidence: 80%
“…Therefore, according to Ntim et al ( 2013 ), we identify the global financial crisis period as 2008–2009. 2 Balli et al ( 2019 ) estimate traveler arrivals by controlling regional structural changes. Eugenio-Martín et al (2004) discover that the nexus between the number of traveler arrivals and economic development does exist in developing nations, but not in developed nations.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the hospitality and tourism sector has been experiencing numerous challenges following the global financial crisis (Kapiki, 2012;Smeral, 2009). Following Hill et al (2015), we thus set the global financial crisis period as 2008-2009. Balli et al (2019 forecast visitor arrivals by controlling regional structural changes.…”
Section: Methodology Datamentioning
confidence: 99%